Grating and plasmon resonances in the scattering of light by finite silver nanostrip gratings - Shapoval, O.V.; Sauleau, R.; Nosich, A.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
We study numerically the H-polarized wave scattering by finite flat gratings of N silver nanostrips in free space in the context of co-existence of surface plasmon resonances (SPR) and periodicity-induced grating resonances (GRs). The accurate numerical analysis is carried out using the previously developed combination of two-side generalized boundary conditions imposed on the strip median lines and Nystrom-type discretization of the relevant singular and hyper-singular integral equations. Our computations are focused on specific periodicity-caused coupling which leads to the existence of the grating or lattice resonances near to λG = p/m, m = 1, 2,… (at normal incidence). These resonances result in large reflection, transmission, absorption, and near-field enhancement. We also study the interplay of SPR and GR, if they approach each other and the optical response dependence of the grating parameters, such as overall dimension and number of strips.